Diagnostic Applications of ?B-Scan? - Ahmad, Mehmood Hussain, Ejaz Ahmed Javed, Aamir Ali Ch, Iftikhar (Pakistan Journal of Ophthalmology, 2007)
Purpose: To evaluate the diagnostic importance of ‘‘B-Scan’’ in opaque media where other routine instrumental producers were unreliable Materials And Methods: The ‘‘B-Scan’’ was done on 463 eyes of 463 patients at Madina Medical Centre, University of Faisalabad, during the period March 2005 to March 2006. There were 339(73.2%) male and 124(26.8%) female patients. The age ranged between 6 months to 80 years. A specialized proforma was developed to record the data. Most of the patients were referred from different clinics and hospitals of the Punjab. Results: The maximum number of the participants had age between 21 years to 30 years. Out of 463 patients 20 had only corneal pathology, 90 had only mature cataract, 60 had only vitreous hemorrhage, 68 had only retinal detachment, 51 tractional retinal detachment, 4 had retinoblastoma, 2 optic nerve anomaly, 2 choroidal pathology, 2 persistent hyperplastic primary vitreous (PHPV).163 patients has multiple signs e.g. corneal pathology, catract, vitreous hemorrhage and retinal detachment. Asteroid hyalosis was seen in 1 patient. Conclusions: B-scan proved to be a valuable diagnostic modality in opaque media and had remarkable prognostic importance.